Irrigated farming systems: using the water footprint as an indicator of environmental, social and economic sustainability. (4th September 2018) - Altobelli, F.; Cimino, O.; Natali, F.; Orlandini, S.; Gitz, V.; Meybeck, A.; Dalla Marta, A.
Abstract: In the current study, for the main crops cultivated in the Campania region (South of Italy), three indicators were proposed and analysed. The blue water footprint (WFb), which gives an indication of the impact of irrigation on the water resource; the gross margin WFb (GMWFb), describing the economic productivity of irrigation; and the job WFb (JWFb) that expresses the social value of blue water in terms of job opportunities. Results confirmed that water applied through irrigation is much higher compared with crop requirements. In terms of GMWFb, silage maize, maize and alfalfa had the highest values, while olive, potato and tomato had the lowest. Concerning JWFb, silage maize was the crop with the highest value. Even though a deeper analysis should be done in terms of added value in the entire supply chain, the results indicated a clear difference between the crops related to animal feeding (alfalfa, maize) and the other crops taken into consideration. In fact, for the former, both the GMWFb and the JWFb achieved their highest values. Results showed that for certain irrigation volumes and for certain crops, the economic and social impacts are very different and the choice of an irrigated crop rather than another has different repercussions in terms of environmental and socio-economic sustainability. The proposed indicators would allow water managers and farmers to assess and compare production systems in terms of the different benefits that their use of water can provide.